The Rise of Christianity : The Byzantine Empire - History (Television network); Arts and Entertainment Network ([New York] : A&E Television Networks, 2010)
Using dramatic reenactments, state of the art cinematography, location shooting, CGI and 3-D animation, historians and experts talk about history from the origins of man to the discovery of a new world.
The Rise of Christianity The Dark Ages Engineering an Empire: The Byzantines Cities of the Underworld: Gods of War ( Turkey)
Title from container.
Multiple hosts and presenters.
DVD, region 1, full screen presentation.
Keywords: World history. -- Eupore -- Turkey; Video recordings for the hearing impaired; Television programs